Identify of Fast-Growing Related Genes Especially in Height Growth by Combining QTL Analysis and Transcriptome in Salix matsudana (Koidz) - Liu, Guoyuan; Yang, Qingshan; Gao, Junfeng; Wu, Yuwei; Feng, Zhicong; Huang, Jingke; Zou, Hang; Zhu, Xingzhao; Chen, Yanhong; Yu, Chunmei; Lian, Bolin; Zhong, Fei; et al. (Frontiers in Genetics, 2021)
The study on the fast-growing traits of trees, mainly valued by tree height (TH) and diameter at breast height (DBH), is of great significance to promote the development of the forest industry. Quantitative trait locus (QTL) mapping based on high-density genetic maps is an efficient approach to identify genetic regions for fast-growing traits. In our study, a high-density genetic map for the F1 population was constructed. The genetic map had a total size of 5,484.07 centimorgan (cM), containing 5,956 single nucleotide polymorphisms (SNPs) based on Specific Length Amplified Fragment sequencing. Six fast-growing related stable QTL were identified on six chromosomes, and five stable QTL were identified by a principal component analysis (PCA). By combining the RNA-seq analysis for the two parents and two progenies with the qRT-PCR analysis, four candidate genes, annotated as DnaJ, 1-aminocyclopropane-1-carboxylate oxidase 1 (ACO1), Caffeic acid 3-O-methyltransferase 1 (COMT1), and Dirigent protein 6 (DIR6), that may regulate height growth were identified. Several lignin biosynthesis-related genes that may take part in height growth were detected. In addition, 21 hotspots in this population were found. The results of this study will provide an important foundation for further studies on the molecular and genetic regulation of TH and DBH.